Analysis of Efficient Optimization Algorithm for Information Nodes in Wireless Network Communication Chaos - Qi, Jing; Cao, Tru (Bright Publisher, 2023)
Due to the poor node optimization effect of traditional mathematical model methods, an efficient node optimization algorithm based on ant colony genetic algorithm is proposed. The ant colony algorithm is a kind of bionic optimization algorithm, and its dynamics and self-similarity are very similar to the optimization principles of messy information nodes.